1998
DOI: 10.1038/nbt0198-33
|View full text |Cite
|
Sign up to set email alerts
|

DNA variation and the future of human genetics

Abstract: The use of DNA variants in the mapping of the human genome and in the positional cloning of monogenic disease genes is well established. Determining the genetic bases of the more common "multifactorial" diseases, however, presents a major challenge. The genetics of these diseases are complicated by the interplay between many genes and the environment. These investigations will require large numbers of DNA markers and the technology to screen large populations with these markers. The systematic identification o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
104
0
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 196 publications
(105 citation statements)
references
References 56 publications
0
104
0
1
Order By: Relevance
“…SNPs have been proposed as the next generation biomarkers for the identification of gene loci associated with various diseases and their complications (Kruglyak 1997;Schafer and Hawkins 1998). Indeed, recent studies revealed the effect of SNPs in IL-27 promoter region on modulating the progression of infectious diseases and the patient's susceptibility to therapeutic response.…”
Section: Discussionmentioning
confidence: 99%
“…SNPs have been proposed as the next generation biomarkers for the identification of gene loci associated with various diseases and their complications (Kruglyak 1997;Schafer and Hawkins 1998). Indeed, recent studies revealed the effect of SNPs in IL-27 promoter region on modulating the progression of infectious diseases and the patient's susceptibility to therapeutic response.…”
Section: Discussionmentioning
confidence: 99%
“…Updates will clearly be needed in the future, and other recent reviews offer alternative opinions. 52,[140][141][142][143] The technology option which is best will be driven by different criteria for different users. The relative importance of upfront and ongoing operational costs and how adaptable and generalizable a technology is will depend on whether one is in an academic biomedical research center, a clinical molecular diagnostics laboratory or the pharmaceutical industry, among other venues.…”
Section: Discussionmentioning
confidence: 99%
“…Instead, techniques for large-scale and massively parallel sequence comparisons are needed. Most established methods, however, cannot easily meet the demands for rapid, cost-effective, and large-scale sequence analysis (see Schafer and Hawkins, 1998), but the high-density format of the DNA array has proven extremely useful.…”
Section: Identifying and Genotyping Dna Variationmentioning
confidence: 99%
“…In addition, sequence variations have served as landmarks throughout the human genome for identifying mutations underlying Mendelian phenotypes. The next step is to extend positional mapping to traits and diseases with complex inheritance patterns (reviewed by Schafer and Hawkins, 1998;Plomin etal., 1994). For this purpose, at least 500,000 allelic variants may need to be identified and catalogued (Kruglyak, 1999;Risch and Merikangas, 1996).…”
Section: Identifying and Genotyping Dna Variationmentioning
confidence: 99%